CEDERA ROTATOR CUFF ATLET PENCEGAHAN DAN PERAWATANNYA - Roy Januardi Irawan, (Ordik, 2010)
The rotator cuff was made up of four muscles that help move and stabilize the shoulder joint. Damage to any one of the four muscles or their ligaments that attach the muscle to bone can occur because of acute injury, chronic overuse, or gradual aging. This can cause significant pain and disability with range of motion or use of the shoulder joint. When the the athlete got injured on his/her rotator cuff, many things that coach and athlete should do. RICE method was the first aid kit that should be taken in order to minimize the pain and make the injured are not spread out. Many things that should be done to minimize the risk of rotator cuff injured and also many things should be done if the athlete got rotator cuff injured. This article is a describe of rotator cuff injured, the cause, the  the symptoms and the treatment when the athlete got the rotator cuff injured.